2005
DOI: 10.1007/s00011-005-1377-2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma interferon: a central mediator in atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the vasculature with lesions developing in the arterial wall, frequently in the coronary and carotid arteries. The interaction between macrophages and lymphocytes within the atherosclerotic lesion microenvironment exemplifies a site where both innate and adaptive immunity contribute towards disease progression. As gamma interferon (IFN-gamma), the classic macrophage activating factor, has been localized to atherosclerotic lesions, this review will focus on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 193 publications
(298 reference statements)
1
81
0
Order By: Relevance
“…9 In this regard, CD4 1 CD28 null T cells secrete high amounts of IFN-c to activate macrophages, which produce metalloproteinases that degrade the extracellular matrix. 23,24 Furthermore, CD4 1 CD28 null T cells release perforin and granzymes that lyse endothelial cells and vascular smooth muscle cells. 25 In our study, we focused on CD8 1 CD57 1 T cells because cardiovascular mortality was independently associated only with the frequency of CD8 1 CD57 1 T cells and found that CD8 1 CD57 1 T cells also demonstrated senescent, pro-inflammatory and highly cytotoxic properties.…”
Section: Discussionmentioning
confidence: 99%
“…9 In this regard, CD4 1 CD28 null T cells secrete high amounts of IFN-c to activate macrophages, which produce metalloproteinases that degrade the extracellular matrix. 23,24 Furthermore, CD4 1 CD28 null T cells release perforin and granzymes that lyse endothelial cells and vascular smooth muscle cells. 25 In our study, we focused on CD8 1 CD57 1 T cells because cardiovascular mortality was independently associated only with the frequency of CD8 1 CD57 1 T cells and found that CD8 1 CD57 1 T cells also demonstrated senescent, pro-inflammatory and highly cytotoxic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although an increased level of IFN-␥ is protective against acute viral infection, excessive production of IFN-␥ by NK cells can lead to increased pathology in the Shwartzman reaction to LPS, inflammatory bowel disease, and atherosclerosis (37)(38)(39)(40)(41)(42). Negative regulators such as ATF3 serve to modulate inflammation to a level appropriate for clearing a pathogen while preventing pathology caused by unrestrained inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Activated CD4 1 Tlymphocytes and macrophages are the predominant cell populations identifiable in atheromatous plaques (35,36). 6 /ml) were primed by incubation with interferon-g (100 ng/ml) for 24 h. After priming, the cells were incubated for 18 h with three different concentrations of OxLDL-ICs prepared with two different OxLDL antibodies with KLH-ICs at a concentration identical to the higher concentration of OxLDL-ICs.…”
Section: Discussionmentioning
confidence: 99%
“…1 T-cells do not fit neatly into the Th1-Th2 pattern, but they release predominantly interferon-g, a cytokine that is believed to play a key role in the development of atherosclerosis (36). This implies that cellmediated and humoral mechanisms may synergize in the atheromatous plaque to enhance the inflammatory reaction.…”
Section: Immune Complexes Containing Oxldl Are Proinflammatorymentioning
confidence: 99%